Escape to Alcatraz: evolutionary history of slender salamanders (Batrachoseps) on the islands of San Francisco Bay - Martínez-Solano, Iñigo (BioMed Central, 2009)
BACKGROUND: Island populations are excellent model systems for studies of phenotypic, ecological and molecular evolution. In this study, molecular markers of mitochondrial and nuclear derivation were used to investigate the evolution, structure and origin of populations of the California slender salamander (Batrachoseps attenuatus) inhabiting the six major islands of San Francisco Bay, formed following the rising of sea level around 9,000 years ago. RESULTS: There was a high degree of congruence in the results of analyses of nucleotide and allozyme data, both of which strongly support the hypothesis that, for the majority of the islands, salamanders are descended from hilltop populations that became isolated with the formation of the Bay ca. 9,000 years ago. There are two exceptions (Alcatraz and Yerba Buena) where the evidence suggests that salamander populations are wholly or in part, the result of anthropogenic introductions. Comparison of the molecular data and the interpretations drawn therefrom with an earlier morphological study of many of the same salamander populations show some of the same evolutionary trends. CONCLUSION: In spite of marked differences between the evolutionary rates of the two kinds of molecular markers, both indicate distinctive and similar patterns of population structure for B. attenuatus in the San Francisco Bay Area and its islands. With the two noted exceptions, it is clear that most island populations were established prior to the 9,000 years since the formation of the Bay. Results of coalescence-based analyses suggest that for most island populations the mtDNA lineages from which they were derived date from the Pleistocene. It can be said that, based on observed values of genetic diversity, the last 9,000 years of evolution on these islands have been characterized by relative stability, with the occasional extinction of some haplotypes or alleles that were formerly shared between island and mainland populations but overall maintaining high levels of variation (with the exception of Alcatraz). In contrast, there is some evidence for rapid morphological changes between populations in some islands and their closest mainland counterparts. This pattern of rapid morphological divergence (e. g., resulting from founder effects) is similar to that observed in other studies about recent colonization of island habitats.